Comparison of the organic compounds composition of Hylobius abietis males and females before and after exposure to Beauveria bassiana infection. (8th January 2020) - Gołębiowski, Marek; Bojke, Aleksandra; Tkaczuk, Cezary; Majchrowska‐Safaryan, Anna; Stepnowski, Piotr
Abstract: In the present study, the lipid composition from male and female Hylobius abietis is analyzed pre‐ and post‐infection with Beauveria bassiana . The compounds are analyzed by gas chromatography‐mass spectrometry. In the lipids of males and females fatty acids, fatty acid methyl esters, alcohols, amino acids and other organic compounds are identified. The lipids of males and females after B. bassiana exposure contain 31 and 33 organic compounds, respectively, whereas the lipids of non‐infected males and females contain 30 and 37 compounds, respectively. The most abundant compounds in infected and non‐infected males are fatty acids: C16:0, C18:0, C18:1 and C18:2. Contents of dominant compounds from the lipids of infected and non‐infected males are similar to those extracted from the lipids of infected and non‐infected females. It should be noted that the total mass of organic compounds is higher in non‐infected insects than infected insects. Abstract : The lipids of males and females Hylobius abietis after Beauveria bassiana exposure contain fatty acids, fatty acid methyl esters, alcohols, amino acids and other organic compounds. Statistically significant differences are found with respect to the contents of organic compounds between control females and those exposed to B. bassiana and between non‐infected males and females. Males are probably more resistant than females to fungal infections because the infection does not affect the composition of lipids of males.